Human Resource Management Practices in Startup Companies: Challenges and Opportunities - Budi Rismayadi (International Publisher, 2024)
This research aims to investigate human resource management (HR) practices in start-up companies and explore the challenges and opportunities faced in this context. The research method used is a qualitative study with descriptive methods. The research results show that human resource management (HR) practices in start-up companies face unique challenges, but also offer significant opportunities for sustainable development. Start-up companies have the advantage of building an inclusive and innovation-oriented work culture, as well as taking advantage of small teams to provide a personal approach to employee development. In addition, technology adoption and partnerships with educational and training institutions are important strategies in improving HR management efficiency and accessing quality talent. Thus, the results of this research highlight the importance of an adaptive and innovative approach in HR management to support the growth and success of start-up companies in a dynamic business environment.